Honey bees (Hymenoptera: Apidae) outnumber native bees in Tasmanian apple orchards: Perspectives for balancing crop production and native bee conservation. Issue 2 (3rd February 2021) - Prendergast, Kit S; Leclercq, Nicolas; Vereecken, Nicolas J
Abstract: Apples are a major crop globally, including in Tasmania (Australia) – known as 'the Apple Isle' owing to the key role of apples in Tasmania's history and economy. Most apple cultivars are obligate entomophilous species, and fruit quantity, quality and economic value are enhanced under insect pollination. Whilst the introduced European honey bee ( Apis mellifera ) is often assumed to be the main pollinator of apple in most regions of the world, including Australia, there is an increasing interest in alternative pollinators. The pollinator community of Tasmanian apple crops, however, has never been assessed. In this study, we surveyed four apple orchards for 3 days each during peak bloom in the Huon Valley region to characterise bee assemblages visiting blooming apple trees and the native bee fauna associated with surrounding flowering vegetation. Our results show that honey bees were the predominant visitors to apple blossoms (90.7% of visits), followed by the introduced bumble bee Bombus terrestris (5.9% of visits), with only a minor contribution by native bees (3.3% of visits). Twenty‐six species of native bees were collected in total, of which only 10 species (five Exoneura (Apidae), four Lasioglossum (Halictidae) and one Euryglossa (Colletidae) species) were collected from apple blossoms, with Exoneura being the most abundant visitors. Few native bees were captured on apple blossoms, however co‐blooming surrounding native vegetation, as well exotic flowers, hosted a high diversity and abundance of native bees. Site conditions influenced community composition, including abundance and representation of introduced bees compared to native bees visiting apples. Additionally, warmer temperatures favoured native bees. Collectively, our results suggest that Tasmania's apple production in its current state is unlikely to rely exclusively on native pollinators. Native bees nevertheless warrant conservation in such an insular crop production system. This can be achievable through retaining native flowering plants and even exotic non‐crop flowers in and around orchards. Promoting the diversity and abundance of native bees through habitat enhancement may have additional benefits, such as filling current and future pollination demands and gaps, a key strategy under scenarios of climate change.